2022
DOI: 10.25259/apos_105_2021
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of orthodontic brackets coated by silver hydroxyapatite, copper oxide, and titanium oxide nanoparticles on wire-bracket friction

Abstract: Objectives: Coating orthodontic brackets with metal nanoparticles seem to affect surface roughness and friction. We aim to compare the effects of coating brackets with copper oxide (CuO), titanium dioxide (TiO2), and silver hydroxyapatite (S-HAP) on friction between brackets and various sizes and materials of orthodontic wires. Material and Methods: In this experimental study, we selected four groups of stainless steel (SS) brackets with eight orthodontic wires (SS and nickel-titanium [Niti]) in different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Metal oxide-based NPs have been used to improve the performance of biocomponent surfaces, particularly as antimicrobial agents for multiple biomedical applications [469]. According to the literature, the following types of metallic oxide NPs have been considered to cover metallic fixed appliances: ZnO- [367,[437][438][439][440][441][442][443]445] and/or CuO-NPs [437,446,447], AlO-NPs [444], TiO 2 -NPs [446][447][448][449], and Ag-HA-NPs [446,447], as presented in Table 9.…”
Section: Metal Oxide-based Nanoparticles Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal oxide-based NPs have been used to improve the performance of biocomponent surfaces, particularly as antimicrobial agents for multiple biomedical applications [469]. According to the literature, the following types of metallic oxide NPs have been considered to cover metallic fixed appliances: ZnO- [367,[437][438][439][440][441][442][443]445] and/or CuO-NPs [437,446,447], AlO-NPs [444], TiO 2 -NPs [446][447][448][449], and Ag-HA-NPs [446,447], as presented in Table 9.…”
Section: Metal Oxide-based Nanoparticles Coatingsmentioning
confidence: 99%
“…Coating physical stability was the main downside: Around 60% of the coating showed adhesion failures [448]. Ameli et al [446,447] showed that TiO 2 -NPs and Cu-NPs coatings on SS brackets deposited by a sol-gel method possessed antibacterial properties and could significantly reduce the friction against metallic archwires. Chaturvedi and colleagues [450] dip-coated β-Ti and NiTi archwires with TiO 2 -NPs using different concentrations and dipping durations.…”
Section: Metal Oxide-based Nanoparticles Coatingsmentioning
confidence: 99%